Increase Reading Skills through the Medium of Cards Wall in Children Aged 4-5 Years in Kindergarten : Peningkatan Kemampuan Membaca Melalui Media Kartu Dinding Pada Anak Usia 4-5 Tahun di TK - Firda Berliantin; Evie Destiana (Universitas Muhammadiyah Sidoarjo, 2022)
Reading is a unity of integrated activities that include a variety of activities, such as recognizing letters and words, connect with the sound, as well as draw conclusions about the intent bacaanya. Based on the experience of the researcher, that most of the children of group A in TK Aisyiyah Bustanul Athfal 1 Temple, the ability to read A group has not been able to achieve optimal development. It required the application of the card media wall to improve reading skills. This research using the Method of Classroom Action Research to improve their reading skills. This study was conducted in 2 cycles. The study was conducted in three stages namely pre-cycle, cycle I and cycle II to obtain the results as expected. In the pre cycle, most children still acquire an average value of 43,0% while in the first cycle the percentage value increases so that the obtained prosentas the value of be is 61.5%, which means less than the maximum. Then the researchers proceeded to give the action in cycle II, after doing research on the second cycle is the percentage of the average value of the child to 84.8%, resulting from the acquisition of the average in cycle I and cycle II increased again. It can be seen from the comparison between cycle I and cycle II during the study. From the results obtained, there is an increase in proving that with the Media Card Wall can improve the reading ability of the children.